O feminino, as mulheres e as infâncias públicas : uma ciranda de pedra? - Werner, Ana Beatriz (2006)
This research deal with the universe of the Childhood and the Younth in the social risk s situations. We can raise the hypothesis that a specific institucional speech about the women circulates over there. Then, several images of the denigrated woman were constituted. These images of the women correspond to the sheltered children s mother. Since the origins of the institutions of shelter for abandoned children, in the advent of Modernity, it already circulated a speech on the women and their maternal s behaviors. They had been accused to leave their children in the doors of the hospices and churches of the Europe of century XVIII, during the dawn, to anyone take care them. "They didn t follow the designs of God", somebody said, they denied to follow their "maternal instinct". Therefore, these women must be out of the bourgeois family s social order. Where could have a place for them in the social speech? The woman who abandons a child comes to occupy a denied place in imaginary collective speech? We search to interrogate what could be changed or be transformed, since the hospices and churches s time until the current institutions of shelters.